Cereals attract wild avian herbivores in wet grasslands – Implications for range management - Karmiris I.; Platis P.; Kazantzidis S.; Papachristou T.G. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
The aim of this paper was to investigate the effectiveness of the broadcast seeding of common wheat (Triticum aestivum) in order to increase the available wintering food for geese species, along the eastern shoreline habitat of the Kerkini Lake, Greece. Seeding wheat increased the total plant cover and subsequently reduced the percentages of the bare soil and the mosses’ cover at about 20%. Herbage biomass was also increased (about 30%) compared to the non-seeding sites. Herbage utilization rates by geese species were increased more than 40% in December, i.e. only two months after the implementation of the seeding process. In conclusion, seeding cereals is a promising management practice in order to increase the availability of food for the avian herbivores during the critical wintering period.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)